Personal and situational factors influencing coaches` perceptions of stress - Knight, C. J.; Reade, I. L.; Selzler, A.-M.; Rodgers, W. M. (Journal of Sports Sciences, 2013)
Coaching has been recognised as a demanding occupation, associated with a range of stressors. The extent to which coaches perceive stress is likely to be influenced by various personal and situational factors. The purpose of this study was to identify coaches' levels of perceived stress and examine the personal and situational factors that may influence coaches' perceptions of stress. In total, 502 coaches working with university, college, Canada Games, and/or nationally identified athletes completed this study. Coaches completed an online survey, which included questions regarding demographics, work/job-related considerations, and aspects relating to their contract. Coaches also completed the Perceived Stress Scale (Cohen, Kamarck, & Mermelstein, 1983). Overall coaches indicated slightly below average levels of perceived stress (M = 15.13 out of 40) compared with norm-values (Cohen & Janicki-Deverts, 2012). Demographic factors, job-related characteristics, and certain aspects of their contract were associated with coaches' perceptions of stress. In particular, unclear expectations, long-working hours (>40), lack of agreed evaluation criteria, higher salaries, and a lack of social support were related to higher perceptions of stress. As such, the findings of the current study indicate that a reduction in perceived stress is likely to be achieved through a multifaceted approach that addresses multiple factors associated with coaching.